PERANCANGAN ULANG LEMARI PENYIMPANAN PRODUK REPAINT PADA UKM SBS GARAGE AND PAINT - Silaban, Riswanto Agustino; Ganda Sirait (Computer Science and Industrial Engineering, 2024)
UKM SBS Garage and Paint is a service business in the field of vehicle painting services in Batam. When finished painting, the painter has a problem, namely large and medium-sized vehicle parts will be left for drying not enough to load into the storage cabinet, so that the drying process time becomes long and the storage cabinet is dirty, so the work process becomes late due to waiting for more time, and makes customers wait due to the delay in time from the agreement then the business location has a small size so that there is a lack of neatness due to the large number of vehicle parts. The purpose of this study was to find out a redesign that can shorten the drying time. The method used in this study is the NIDA (Need, Idea, Decision and Action) method. The result of this study is to get a design choice as needed (need) is an alternative with action, namely increasing the size of the cabinet with 180cm x 80cm x 180cm (length x width x height) with the use of iron and aluminum materials with the addition of 4 wheels and 8 pieces of incandescent lamps. After data analysis and data testing, the results obtained that the old storage cabinet can cover a temperature of 25 ° C - 30 ° C with an output of 5 per day, while after redesign get a room temperature result of 45 ° C - 50 ° C with an output of 33.6 per day.